Height Estimation Based on Foot Length and Breadth in Children, Teenager, and Adult in Bandung City, Indonesia - Sani Tanzilah; Noorman Herryadi; Andri A. Rusman (Universitas Kristen Maranatha, 2016)
Stature estimation is important for forensic identification, particularly in dismembered body. The equation used to estimate the height of a population is not necessarily applicable to other populations (population spesific). This study was conducted to generate the linear regression equation for stature estimation based on foot length and foot breadth on the population in the city of Bandung.Â This cross-sectional study is conducted to 908 people, consisting of three age groups (children, adolescents, adults), in the city of Bandung. Sampling was done by multistage sampling. The stature was measured using a stadiometer SECA 213, right foot length (RFL), right foot breadth ( RFB), left foot length (LFL), and left foot breadth (LFB) were measured using sliding calipers. Data were analyzed with SPSS version 21.0 for Windows. There is correlation between height with the RFL, RFB, LFL, and LFB. In contrast to the group of teenagers and adults, there is no boys-girls difference between height, RFL, RFB, LFL, and LFB. 21 regression equation for stature estimation based on the foot size. Stature estimation can be done using the linear regression equation based on the foot length and foot breadth, according to population, gender, and age of the subject being examined.Â Key words: height estimation, foot length, foot breadth